Coconut breeding: Papers presented at a workshop on standardization of coconut breeding research techniques, 20-25 June 1994, Port Bouet, Côte d'Ivoire - Batugal, P.A.; Ramanatha Rao, V. (1998)
One of the major problems of coconut farmers is the lack of well-adapted and high yielding coconut varieties. Other related problems are the insufficient number of well-trained coconut breeders and efficient breeding research techniques to develop improved varieties. On 20-25 June 1994, GTZ, BUROTROP and IPGRI supported a workshop on Standard Research Techniques in Coconut Breeding which was hosted by the Marc Delorme Station Cocotier in Port Bouet, Cote d'Ivoire. Representatives from 16 coconut-producing counties and partner organizations participated in this workshop. The workshop discussed and drafted recommended coconut breeding research techniques which were subsequently refined by IPGRI and published as a ”Manual on standardized research techniques in coconut breeding” (STANTECH Manual). The manual has been used by IPGRI/COGENT to train 50 trainers worldwide who are expected to train additional national coconut breeders. In the same workshop, participants also presented the coconut breeding programmes being implemented in their home countries. The participants noted the range of germplasm available for breeding and exchanged experiences on how to increase efficiency in developing improved varieties. Most of these papers were updated in 1998 to reflect modifications in respective programmes. The updated papers are presented in this publication.